Numerical Evaluation of Nonlinear Response of Broad Cylindrical Steel Tanks under Multidimensional Earthquake Motion - Ozdemir, Zuhal; Souli, Mhamed; Fahjan, Yasin M. (Earthquake Engineering Research Inst, 2012)
In this paper, a fluid-structure interaction (FSI) algorithm of the finite element method (FEM), which can take into account the effects of geometric and material nonlinearities of the tank, buckling of the tank shell, and nonlinear sloshing behavior of the contained liquid, is utilized to evaluate the actual behavior of broad cylindrical steel tanks when subjected to strong earthquake motions. In order to clarify a key question-whether anchoring would prevent earthquake damage to tanks-numerical analyses are carried out on the same tank model having two different support conditions: anchored and unanchored. In addition to two horizontal components of ground motion, the vertical component is also taken into account in order to determine the relative importance of vertical ground motion in the behavior of tanks. The consistency of provisions presented in current design codes and numerical analysis results is evaluated. [DOI:10.1193/1.3672996]
Keywords: buckling; earthquake engineering; finite element analysis; shapes (structures); sloshing; tanks (containers)